Static and quasi-static routing in integrated services digital networks - Grzech, Adam; Kasprzak, Andrzej (1953- ) (Zielona Góra: Uniwersytet Zielonogórski)
The aim of this paper is to formulate, discuss and solve some selected problems concerning routings problems in the Integrated Services Digital Network. The problems under consideration are restricted to routes in the ISDN over which both voice calls and data streams are transmitted using circuit- and packet-switched transmission modes.
Keywords: sterowanie; sterowanie-teoria; sztuczna inteligencja; matematyka stosowana; informatyka